Plants that allocate more resources to flower production yield more fruit at local and global scales - Barrero-Flores, Valentina (2026)
Introduction: The internal mechanisms of plants and their interactions with the environment determine flower and fruit production. Several hypotheses have been proposed to explain these processes, emphasizing resource limitations, interactions with pollinators, selective abortion, the characteristics and positions of hermaphroditic flowers, and the influence of environmental variables on plant function. Objectives: This research aims to evaluate whether a high allocation to flowers positively affects the fruit production of hermaphroditic plants, as predicted by the pollinator attraction hypothesis, or whether it negatively correlates, as suggested by the selective abortion hypothesis. Methods: Both a local (Medina, Colombia) and a global database, based on the biomass of flowers and fruits collected using fruit traps were used to determine the possible relationship between the variables. The Medina database included data from 5-10 individuals for each of the seven plant species studied, with entire flowering and fruiting periods monitored. The global dataset encompassed 92 locations across 10 counties in Latin America, 2 in Europe, 2 in Africa, 2 in Asia and 1 in Oceania. This database compiled information on the total biomass of flowers and fruits of different plant species produced over at least one annual cycle. Results: The plant species studied and the global analysis revealed a positive relationship between flower and fruit production, supporting the pollinator attraction hypothesis. Although we did not quantify the biomass of aborted fruits, we found no evidence to suggest that high flower production results in an excess of ovules that cannot develop, as predicted by the selective abortion hypothesis. Conclusions: These findings suggest that plants have evolved allocation mechanisms for flower production that align with the potential for fruit development.